A mechanical study of personalised Ti6Al4V tibial fracture fixation plates with grooved surface by finite element analysis. Issue 3 (12th August 2021) - Liao, Bo; Sun, Jipeng; Xu, Cheng; Xia, Rufeng; Li, Wei; Lu, Dong; Jin, Zhongmin
Abstract: Low shape matching and high stress shielding rates between bone plate and human bone are not conducive to the primary healing of fracture. In this study, taking the fracture site of the lower one‐third of human tibia as an application case, six types of personalised Ti6Al4V tibial plates with grooved surface were designed and evaluated by reverse engineering and finite element analysis. The results showed that the grooved design can reduce the stress shielding rate of bone plate and promote the facture healing. Among the six types of bone plates, the 'OUT‐MI' bone plate has the lowest stress shielding rate and the most uniform stress distribution. Meanwhile, with the increasing tibial load during the convalescence, the average stress and maximum axial displacement of the tibial fracture surface increased, which can effectively improve the bone regeneration in the tibial fracture area. Moreover, there was no significant difference in four‐point bending performance between the 'OUT‐MI' bone plate and the 'STR‐BE' bone plate, indicating that the mechanical properties of this bone plate were reliable. The results provide a theoretical basis for the design of fracture fixation plates on clinical treatment.